Sagot :
ANSWER:
B. True
Step-by-step explanation:
f(x)=ax^2+bx+c
Removing a out of the first two terms
=a(x^2+b/a x) + c
Adding zero
=a(x^2+b/a x +b^2/4a^2 - b^2/4a^2) + c
Removing one of the added terms ozt of the bracket
=a(x^2+b/a x +b^2/4a^2) + c - b^2/4a
Using the first binomial rule backwards
=a(x+b/2a)^2 + c - b^2/4a
Comparing with the vertex form
f(x)=a(x-xV)^2+yV
we see that the vertex lies at
VP(-b/2a, c-b^2/4a)
So the vertex x position is at -b/2a and that is the symmetry line for a quadratic function.